Cesium Carbonate-Promoted P-Alkylation of Phosphinecarboxamides - Chen, Xing-Guo; Wu, Qiu-Li; Hou, Fei; Wang, Xi-Cun; Quan, Zheng-Jun (Synlett, 2019)
An effective method for the P-alkylation of N-arylphosphinecarboxamides was demonstrated. Primary N-arylphosphinecarboxamides without additional protection underwent P-monoalkylation with various alkyl halides in the presence of cesium carbonate as a promoter. The reactivity of phosphinecarboxamides was also explored.
Keywords: alkylation; phosphinecarboxamides; arylalkylphosphinecarboxamides; secondary phosphines; alkyl halides